Targeting the IGF-1R: The Tale of the Tortoise and the Hare - Crudden, Caitrin; Girnita, Ada; Girnita, Leonard (Frontiers in Endocrinology, 2015)
The insulin-like growth factor type 1 receptor (IGF-1R) plays a key role in the development and maintenance of cancer. Since the first links between growth factor receptors and oncogenes were noted over three decades ago, targeting the IGF-1R has been of great interest. This review follows the progress from inception through intense pharmaceutical development, disappointing clinical trials and recent updates to the signaling paradigm. In light of major developments in signaling understanding and activation complexities, we examine reasons for failure of first line targeting approaches. Recent findings include the fact that the IGF-1R can signal in the absence of the ligand, in the absence of kinase activity and utilizes components of the GPCR system. With recognition of the unappreciated complexities that this first wave of targeting approaches encountered, we advocate recognition of IGF-1R as a valid target for cancer treatment and look to future directions, where both research and pharmaceutical strengths can lend themselves to finally unearthing anti-IGF-1R potential.